2019
DOI: 10.1186/s12885-019-6045-y
|View full text |Cite
|
Sign up to set email alerts
|

Lipid accumulation impairs natural killer cell cytotoxicity and tumor control in the postoperative period

Abstract: Background: Natural killer (NK) cell dysfunction following cancer surgery has been shown to promote metastases. Recent studies demonstrate an emerging role for lipids in the modulation of NK cell innate responses. However, the mechanisms involved in lipid modulation of NK cell postoperative anti-tumor function are unknown. This current study will determine whether the lipid accumulation via scavenger receptors on NK cells is responsible for the increase in postoperative metastasis. Methods: Lipid content in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…The authors showed that, prior to diagnosis of breast cancer, postmenopausal women had significantly higher levels of lipolysis byproducts, free fatty acids (palmitic, arachidonic, stearic, linoleic, oleic acids), and glycerol in their plasma as In the susceptible breast stroma, we observed a downregulation of genes involved in the immune response, an increase in resting NK-related gene signature and a reduction in the IHC staining of CD45 (generic immune marker) and CD20 (B-cell marker) cells. The number and function of the local immune cells can be affected by metabolites released in the surrounding microenvironment [37][38][39] . Recent reports indicate that breast cancer cells may escape immune surveillance by releasing free fatty acids, which inhibit cytotoxic T cells 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that, prior to diagnosis of breast cancer, postmenopausal women had significantly higher levels of lipolysis byproducts, free fatty acids (palmitic, arachidonic, stearic, linoleic, oleic acids), and glycerol in their plasma as In the susceptible breast stroma, we observed a downregulation of genes involved in the immune response, an increase in resting NK-related gene signature and a reduction in the IHC staining of CD45 (generic immune marker) and CD20 (B-cell marker) cells. The number and function of the local immune cells can be affected by metabolites released in the surrounding microenvironment [37][38][39] . Recent reports indicate that breast cancer cells may escape immune surveillance by releasing free fatty acids, which inhibit cytotoxic T cells 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of lipid homeostasis, Raichur S et al showed the opposite expression patterns, where repressed RORC activity induces expression of Cd36. In both animal and human studies, increased Cd36 expression in metabolically active tissue has been implicated in the regulation of fatty acid metabolism and lipid accumulation [35,36]. In HCC patients, the number of fatty acid responsive TFs, including HIF1α and FOS, can transcriptionally upregulate Cd36, which is closely associated with induction of epithelial-mesenchymal transition (EMT) [37].…”
Section: Discussionmentioning
confidence: 99%
“…10 Both M-MDSCs and G-MDSCs are present in distant organs and contribute to premetastatic niche formation after surgery. 11,12 A premetastatic niche is a premetastatic microenvironment in distant organs that is characterized by immunosuppression, inflammation, angiogenesis, and vascular permeability, organotropism, lymph-angiogenesis, as well as reprogramming. 13 Primary cancers induce premetastatic niches in the lungs and liver.…”
Section: Mdscs and Their Roles In Premetastatic Niche Formationmentioning
confidence: 99%
“… 10 Both M-MDSCs and G-MDSCs are present in distant organs and contribute to premetastatic niche formation after surgery. 11 , 12 …”
Section: Mdscs and Their Roles In Premetastatic Niche Formationmentioning
confidence: 99%
See 1 more Smart Citation